The Borg – Glimpsing into a Nietzschean transhumanist utopia (Annals of the University of Bucharest. Philosophy Series, 2025)
Transhumanism is a cultural and philosophical movement that advocates for the use of technology to improve the human condition and overcome limitations as a species. The question of whether the transhumanist goal of a posthuman future is desirable remains open, as it depends on the values and goals that guide the process of technological enhancement. The essay inspects what it would mean to utilize nietzschean values and goals within the process of technological enhancement. Eventhough some consider Nietzche to be a proto-transhumanist, there is more then ample reason to believe that such an association is misguided. The argument presented here highlights why we need to avoid imbuing the goals of transhumanism with nietzschean values. To argue for the dangers inherent in nietzschean ideal the current work draws upon Losurdo and highlights the strongly Reactionary elements that can be found within Nietzsche's philosophy. Next the paper presents how by adding the Borg is a good representation of a society that has added technological enhancements upon a foundation of nietzschean ideal and encourages the abandonment of such utopian aspirations.
Keywords: Transhumanism; Nietzsche; Borg; Utopia; Reactionist